2012
DOI: 10.1177/0333102412458075
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of head pain in response to an experimental cold stimulus to the palate: An observational study of 414 volunteers

Abstract: IH is predominantly frontotemporal, bilateral and throbbing, most commonly affecting migraine sufferers, and the ICHD-II criteria are insufficient for classifying all individuals. We should, however, recommend caution regarding such a generalization from our findings with experimentally provoked cold stimulus headache to cold stimulus headache in general (i.e. HICS, ICHD-II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 22 publications
6
43
0
1
Order By: Relevance
“…One study showed no gender-specific prevalence of ICH [7] whereas another experimental study revealed a higher prevalence of ICH in female than in male migraine patients [11]. The higher prevalence of ICH in adult females seems to be in line with the higher prevalence of other headaches in females compared to males.…”
Section: Gender-specific Prevalencementioning
confidence: 92%
See 3 more Smart Citations
“…One study showed no gender-specific prevalence of ICH [7] whereas another experimental study revealed a higher prevalence of ICH in female than in male migraine patients [11]. The higher prevalence of ICH in adult females seems to be in line with the higher prevalence of other headaches in females compared to males.…”
Section: Gender-specific Prevalencementioning
confidence: 92%
“…Prevalence of ICH in self-assessment questionnaire studies ranged from 8 % [2] to 23 % [3] and 40.6 % [4] up to 79 % [5]. The prevalence rates of experimental induced ICH by cold stimulus ranged from 8 % [6] to 37 % [7]. Most questionnairebased studies did not specify gender distributions in ICH [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HICS is one of the most common primary headache disorders with a prevalence ranging from 38.3% to 79% in children and 5.9% to 74% in adults (2)(3)(4)(5)(6)(7)(8). Various studies have investigated HICS by different experimental approaches (3,4,(8)(9)(10)(11)(12)(13). Three studies used ice cubes of different sizes to provoke HICS (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%